THE TRADITIONAL ELECTRONIC STUDY RESOURCES TO THE TOPICS OF LINEAR ALGEBRA - ORSZAGHOVA, Dana (Journal of Technology and Information Education, 2012)
In the paper we deal with actual topic of the didactic research in the theory of education that includes the application of IT tools in the modern mathematics teaching and in the individual study. Chapters on linear algebra belong to the important parts of the compulsory mathematical subjects. We focused on this mathematical topic and present what kinds of traditional and electronic study resources can use students of the Slovak University of Agriculture in Nitra in their study. In the next section it is presented an overview of study results in the first year of the bachelor study at the Faculty of Economics and Management, which is an indicator of the quality of the mathematics education.
Keywords: teaching of mathematics; linear algebra; test results; electronic study materials; LMS MOODLE